Female Participation In Labour Force: The Success In Reducing Income Disparity In Malaysia - Asmah Mohd Jaapar; Nurhatiah Ahmad Chukar; Hani Zulaikha Hasnul Hisham (Zes Rokman Resources, 2024)
Malaysia has shown an increasing trend of labour force participation rates across different ages and gender since independence in 1957. This includes a rapid increase in women participation in the labour force across all ages. Female higher participation in labour force has significant impact to economic growth and socio-economic development. World Bank has urged Malaysia to increase women participation in labour force to boost the economic growth. Therefore, it become a national agenda in Twelfth Malaysia Plan (2021-2025) to further increase working female population to 59 percent by 2025. Noting the important of the issue in international and national avenue, this study motivated to investigate the impact of women involvement in the labour market in promoting more equitable income distribution in Malaysia. The study employs the Autoregressive Distributive Lag (ARDL) approach to study the short-run and long-run effects of female participation in the labour force to reduce the income gap in Malaysia. The model includes other macroeconomic factors such as economic growth rate, GDP per capita, inflation rate and unemployment rate. This study uses annual time series data from 1970 up to 2019. The result shows that female participation in the labour market significantly reduces the income gap in Malaysia both in the short and long run. The study proves that working women have significantly contributed to the Malaysian economy over the long run. Women improvement in education level and steady increment in labour participation level has improved their economic standing which consequently narrowed the national income gap.